“Cualquier movimiento revolucionario podrá contar con Cuba”: la construcción del nacionalismo internacionalista cubano durante el Año de la Solidaridad (1966) - Alberto García Molinero (Historia Crítica)
Objective/context: This article deepens the conceptualization of the historical phenomenon called "Cuban internationalist nationalism," framed in the so-called Year of Solidarity (1966) and inaugurated with the Tricontinental Conference held in Havana during the height of the Cold War. Metodologia: We propose an interdisciplinary analytical approach, which combines the study of the history of daily life and oral history, embodied in various testimonies, with unpublished documentary sources. Originality: The singularity of this text lies in the conceptual hypothesis manifested in the notion of "internationalist nationalism," constituted at the time of the extended 1960s. The novelty of such a historical look grants a marked ground-breaking character to the present article: the notion is rescued and analyzed from hitherto unknown voices coming from diverse spheres of Cuban society and partially explored repositories, such as Archivo Histórico del Instituto Cubano de Amistad con los Pueblos or Archivo Histórico de la Organización de Solidaridad de los Pueblos de África, Asia y América Latina, known (by its Spanish acronym) as the ospaaal. Conclusions: The article confirms the existence of a marked international projection within the Cuban national sentiment. This internationalist nationalism had a strong imprint on the configuration of the revolutionary identity from its origins to our times, as revealed by the accounts of personalities imbued within this reality. In the framework of the most immediate present, despite the significant global geopolitical transformations that have taken place since the end of the Cold War, this international spectrum continues to be a central pillar in contemporary Cuban society in the face of the multiple challenges it faces in the 21st century.